The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1051/0004-6361:20042530
|View full text |Cite
|
Sign up to set email alerts
|

B-type supergiants in the SMC: Chemical compositions and comparison of static and unified models

Abstract: Abstract. High-resolution UCLES/AAT spectra are presented for nine B-type supergiants in the SMC, chosen on the basis that they may show varying amounts of nuclear-synthetically processed material mixed to their surface. These spectra have been analysed using a new grid of approximately 12 000 non-LTE line blanketed  model atmospheres to estimate atmospheric parameters and chemical composition. The abundance estimates for O, Mg and Si are in excellent agreement with those deduced from other studies, whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
135
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(151 citation statements)
references
References 50 publications
16
135
0
Order By: Relevance
“…Details of the methods adopted can be found in Hunter et al (2007), while a more detailed discussion of the grids can be found in Ryans et al (2003), Dufton et al (2005) 2 . Here only a brief summary will be given, with further details available as discussed above.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the methods adopted can be found in Hunter et al (2007), while a more detailed discussion of the grids can be found in Ryans et al (2003), Dufton et al (2005) 2 . Here only a brief summary will be given, with further details available as discussed above.…”
Section: Methodsmentioning
confidence: 99%
“…The validity of such an approach was investigated by Dufton et al (2005), who analysed the spectra of B-type Ia supergiants in the SMC using the current grid and also theoretical spectra generated by the  code (Santolaya-Rey et al 1997;Puls et al 2005), that incorporates wind effects. Dufton et al (2005) found excellent agreement in the atmospheric parameters estimated from the two methods. Effective temperature estimates agreed to within typically 500 K, logarithmic gravities to 0.1 dex and microturbulent velocities to 2 km s −1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming that all elements with an ionization potential lower than that of hydrogen and oxygen are fully ionized delivers an upper limit of q Metals < 9.5×10 −5 . For this, we used an SMC metallicity of 20% solar (see, e.g., Dufton et al 2005), and solar abundance values for the metals from Grevesse & Sauval (1998). This very low value obtained from the metals means that if hydrogen is ionized by only 1%, it still provides the dominant quantity of free electrons.…”
Section: Outflowing Disk Modelmentioning
confidence: 99%